Celine, a long interspersed nuclear element retrotransposon, colonizes in the centromeres of poplar chromosomes - Xin, Haoyang; Wang, Yiduo; Zhang, Wenli; Bao, Yu; Neumann, Pavel; Ning, Yihang; Zhang, Tao; Wu, Yufeng; Jiang, Ning; Jiang, Jiming; Xi, Mengli (Plant physiology, 2024)
Centromeres in most multicellular eukaryotes are composed of long arrays of repetitive DNA sequences. Interestingly, several transposable elements, including the well-known long terminal repeat centromeric retrotransposon of maize (CRM), were found to be enriched in functional centromeres marked by the centromeric histone H3 (CENH3). Here, we report a centromeric long interspersed nuclear element (LINE), Celine, in Populus species. Celine has colonized preferentially in the CENH3-associated chromatin of every poplar chromosome, with 84% of the Celine elements localized in the CENH3-binding domains. In contrast, only 51% of the CRM elements were bound to CENH3 domains in Populus trichocarpa. These results suggest different centromere targeting mechanisms employed by Celine and CRM elements. Nevertheless, the high target specificity seems to be detrimental to further amplification of the Celine elements, leading to a shorter life span and patchy distribution among plant species compared with the CRM elements. Using a phylogenetically guided approach, we were able to identify Celine-like LINE elements in tea plant (Camellia sinensis) and green ash tree (Fraxinus pennsylvanica). The centromeric localization of these Celine-like LINEs was confirmed in both species. We demonstrate that the centromere targeting property of Celine-like LINEs is of primitive origin and has been conserved among distantly related plant species.
Keywords: histony; Retroelements; Phylogeny; Populus; Long Interspersed Nucleotide Elements; Histones; dlouhé rozptýlené jaderné elementy; centromera; retroelementy; fylogeneze; chromozomy rostlin; Centromere; Chromosomes, Plant